LAMELLA : feminine jouissance. - Gonzatto, Camila; Łuczak, Adam; Sachenko, Vira; Brenner, Leon S. (Berlin : Lacanian Affinities Berlin (LAB), 2020)
Berlin, Mira ; Borda, Maite ; Brenner, Leon ; Dushy, Shira ; Gonzatto, Camila ; Janda, Alex ; Karavela, Iro ; Kashirskaya, Lena ; Khan, Razak ; Krause, Rachel B. ; Laurie, Larissa ; Lewis, Jules ; Łuczak, Adam ; Prado, Luiza ; Sachenko, Vira ; Lee, Zihern ; Schmidt-Herzog, Lisa ; Streva, Juliana
The Lamella zine is a publication bringing together the work of the members of the long-standing Lacan Guided Reading Group and Lacanian Affinities Berlin (laLAB). The zine embodies artistic expressions, fabrications, ruminations, critiques and conclusions revolving around the group’s work on the subject of Lacanian psychoanalysis. The “lamella” is a mythical depiction of the Freudian “libido” conceived by Jacques Lacan. The myth of the lamella portrays libido as an uncanny disembodied organ, shed by the living being at the moment of sexual reproduction. It is an organ, since it is an instrument of the organism. However, it is an “unreal” organ, lacking mass or substance, an indefinitely malleable and indestructible surface that perpetually traverses the body’s instincts of survival. (provided by publisher)
boek